Reducing Environment Pollution by Reusing of Alum Sludge Waste in Stone Mastic Asphalt Mixtures - Mahmood, Omar T. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2021)
Globally, a huge quantity of alum sludge waste is produced as a by-product material from drinking water treatment plants that utilize aluminum salts as an essential coagulate and is the most generally produced water treatment remaining sludge around the world, which causes a serious environmental problem. Direct discarding of this substance has ecological effects. Hence, it is important to reuse this alum sludge waste material in such a manner to diminish its detrimental impacts on the environment. This research investigates the possibility of reusing alum sludge waste as a partial replacement of cement filler in stone mastic asphalt (SMA) paving mixtures. For this investigation, the alum sludge was used as a filler material in SMA mixtures in two modes; dried alum sludge at 110°C and burned alum sludge at 700°C. Different percentages of alum sludge were used as a replacement by the total weight of mineral filler at 0, 20, 40, 60, 80, and 100%. The results showed that using alum sludge as a substitution of filler in SMA mixtures reduces the performance of the mixtures in terms of Marshall properties and tensile strength for both dried and burned alum sludge compared with a standard mix. However, the performance of the mixtures containing burned alum sludge gave a better performance than the mixtures containing dried alum sludge.